2016
DOI: 10.1007/82_2016_48
|View full text |Cite
|
Sign up to set email alerts
|

Two Feet on the Membrane: Uptake of Clostridial Neurotoxins

Abstract: The extraordinary potency of botulinum neurotoxins (BoNT) and tetanus neurotoxin (TeNT) is mediated by their high neurospecificity, targeting peripheral cholinergic motoneurons leading to flaccid and spastic paralysis, respectively, and successive respiratory failure. Complex polysialo gangliosides accumulate BoNT and TeNT on the plasma membrane. The ganglioside binding in BoNT/A, B, E, F, G, and TeNT occurs via a conserved ganglioside-binding pocket within the most carboxyl-terminal 25 kDa domain H, whereas B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 189 publications
0
58
0
4
Order By: Relevance
“…Sequence analysis and structural alignment show that the ganglioside-binding site (GBS) motif ‘E…H…SXWY…G’, which is highly conserved in BoNT/A, B, E (residue H is replaced by a K), F, and G (residue E is replaced by a Q) [34], is strictly conserved in H C HA (E1195, H1245, S1256, W1258, Y1259, and G1271) (Figure 2A, green stars). Interestingly, our sequence alignment shows that the H CC of BoNT/HA is most similar to BoNT/A8 (~95%).…”
Section: Resultsmentioning
confidence: 99%
“…Sequence analysis and structural alignment show that the ganglioside-binding site (GBS) motif ‘E…H…SXWY…G’, which is highly conserved in BoNT/A, B, E (residue H is replaced by a K), F, and G (residue E is replaced by a Q) [34], is strictly conserved in H C HA (E1195, H1245, S1256, W1258, Y1259, and G1271) (Figure 2A, green stars). Interestingly, our sequence alignment shows that the H CC of BoNT/HA is most similar to BoNT/A8 (~95%).…”
Section: Resultsmentioning
confidence: 99%
“…However, earlier mice studies confirmed that TeNT effects were not affected by prior immunization in mice [13]. It is possible that the exceptional high affinity to the neuronal membrane of TeNT and a resulting rapid binding to motor neurons [32][33][34] results in a lower probability for a binding to circulating TeNT antibodies. It has furthermore been speculated that antibodies may neutralize only that minor proportion of TeNT, that get into the bloodstream, thus preventing generalized symptoms [13].…”
Section: Discussionmentioning
confidence: 98%
“…After entering the general circulation, TeNT and BoNTs bind with high affinity to the presynaptic membrane of the motor neuron at the neuromuscular junction (NMJ) where they are rapidly internalised (Montal, 2010;Rummel, 2016) ( Figure 1A). BoNTs mainly remain at the NMJ and inhibit the release of the excitatory neurotransmitter acetylcholine (Figure 1), blocking muscle excitation-contraction coupling and thus causing a flaccid paralysis.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…The differences in clinical symptoms arise from preferential site of action in different neurons (Montal, 2010;Rummel, 2016) (Figure 1).…”
Section: Mechanism Of Actionmentioning
confidence: 99%